Analisis Strategi Konsep Smart Tourism Pada Dinas Pariwisata dan Ekonomi Kreatif DKI Jakarta - Widodo, Bambang; Dasiah, Ainisyah Nur (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
Compared to other cities in the world, Jakarta as the capital city of Indonesia is lagging behind in the application of smart tourism, which is part of tourism 4.0. This study aims to find out the right strategy in implementing the concept of smart tourism in Jakarta. This type of research uses descriptive qualitative with data analysis techniques using SWOT and PEST matrices, this research data is obtained using purposive sampling technique with secondary data in the form of website information, digital applications and mobile applications at the DKI Jakarta tourism and creative economy office. The results of the research from the descriptive methodology of SWOT analysis can be obtained values ​​in quadrant I with a matrix value of 2.68 internal factors and a matrix value of 2.65 external factors. Meanwhile, from the PEST analysis, all external factors have a very high influence. From the results of the study it was concluded that progressive tactics are very suitable to be used in the application of smart tourism in Jakarta, meaning that the development of smart tourism is in prime and good condition, so it is really possible to continue to improve, enlarge existing opportunities and achieve maximum progress. Keywords: Smart Tourism, SWOT Analysis, Jakarta Tourism